HIDUP MARADEKA DALAM TATA RUANG RUMAH BUGIS - Hartawan Madeali (Jurnal Koridor, 2018)
Maradeka life is the highest idea of Bugis ethnic in South Sulawesi Province. Life and maradeka terminology are a unity which is found by exploring Bugis script called lontaraq.The research topic is learning from Bugis in planning and design space. The main objective of this study was to reveal the basic consideration of Bugis ethnic in space design which is applied in they traditional house. The research method is historical interpretation and logical argumentaion. Historical interpretation to reveal the meaning of maradeka in script. Logical argumentation to reveal local knowledge in space problem solving for human better life. The script which used to explain maradeka derived from lontaraq Meong Mpalo and lontaraq Attoriolonge Ri Wajo. The study results that Bugis house space design for maradeka life. The application of maradeka life is suitable to vertical space arrangement in Bugis house. The highest space in Bugis house function as food stuff storage as life warranty. The lowest space function as the support of daily life. The human space placed in the middle of life warranty and support of daily life. This space composition suitable to used as basic consideration in macro planning too. Good planning should be prepared space for food stuff, space for living, and space for supporting life. This spaces should be interconnected and proportional to regard for humanity.